Implementasi Pengelolaan Arsip melalui Kegiatan Pengawasan Internal Kearsipan di Puslatbang PKASN Lembaga Administrasi Negara RI - Zakaria, Muhammad Aldodo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Archival supervision aims to ensure that records management is carried out correctly by the creating institution in accordance with the legal basis and applicable rules, one of these institutions is Puslatbang PKASN LAN RI. This study aims to determine the effectiveness and impact of archival supervision activities on records management practices in the Puslatbang PKASN LAN RI work unit, as well as identify the specific contribution of this supervision in improving the efficiency, accuracy, and integrity of records management. In this research, the method used is a descriptive method with a qualitative approach. The data collection process was carried out in 3 ways, namely through interviews, observation, and literature review. As for deciphering data information using stages, namely data reduction, data description and conclusion drawing (verification). The results of this study indicate the role of internal archival supervision on the effectiveness of internal records management at Puslatbang PKASN LAN RI. Obtaining the maximum value in the aspect of dynamic records management and obtaining the final grade of internal archival supervision with the “AA” (Highly Satisfactory) category for three consecutive years (2021, 2022 and 2023). With a percentage of benefits for ensuring records management according to standards (85.7%) and accelerating decision making (85.7%), increasing archive accessibility, awareness of the importance of archives (71.4%), and understanding and smooth administration (57.1%). Archival supervision is significant in ensuring compliance with the rules of the applicable archival regulations, so as to achieve good records management according to the administrative objectives of the agency.